Pemberdayaan Masyarakat Dalam Pengembangan Wisata Desa Kuta Jungak Kecamatan Siempat Rube Kabupaten Pakpak Bharat Provinsi Sumatera Utara - Mayolita Panjaitan; R. Hamdani Harahap; Hadriana Marhaeni Munthe (PERSPEKTIF, 2023)
The purpose of this study was to analyze the process and stages of empowerment carried out by the Tourism and Culture Office of Pakpak Bharat Regency to Pokdarwis Mersada Asa Maju in developing Kuta Jungak village tourism. The research method used in this study is a qualitative method with a descriptive approach. The results showed that the concept of community empowerment has been applied in the village of Kuta Jungak. The empowerment program was carried out by the Pakpak Bharat Regency Tourism and Culture Office to the Mersada Asa Maju Pokdarwis. The concept of community empowerment through the awareness stage, capacity stage and empowerment stage. Community empowerment in the development of Kuta Jungak village tourism, is characterized by the existence of supporting factors and inhibiting factors. The supporting factors consist of: the village head, the potential of Kuta Jungak village, local wisdom, institutions, security and order in the village of Kuta Jungak and the BUMDes of Kuta Jungak. While the inhibiting factors include facilities and infrastructure (consisting of access to tourist objects, signs or directions, cleaning facilities), lack of motivation, funds and budget, human resources include knowledge, skills, ethics and community behavior